2010
DOI: 10.1007/s10597-010-9335-z
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Perceptions of Assertive Community Treatment Interventions

Abstract: The issue of coercion in community-based mental health programs is frequently linked to the development of the Assertive Community Treatment (ACT) model. Sixty-five adults diagnosed with severe and persistent mental illness, participating in an ACT model program, completed measures that assessed elements of coercion and the perceived frequency of use of ACT staff therapeutic limit setting activities, as well as the relationships between coercion, empowerment, quality of life, and the working alliance. On avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Studies have reported that ACT providers sometimes use assertive and controlling techniques. However, supportive relationships and interpersonal influence have been described as the most frequently used mechanisms for promoting treatment goals [ 43 , 47 – 49 ]. As some other studies of ACT show, most participants in our study reported that motivational interventions, persuasion, verbal guidance, and education were more frequently used than threats and force [ 43 , 47 – 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that ACT providers sometimes use assertive and controlling techniques. However, supportive relationships and interpersonal influence have been described as the most frequently used mechanisms for promoting treatment goals [ 43 , 47 – 49 ]. As some other studies of ACT show, most participants in our study reported that motivational interventions, persuasion, verbal guidance, and education were more frequently used than threats and force [ 43 , 47 – 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the scale has been adapted to outpatient treatment and CTO. The Perceptions of Mental Health Services Questionnaire (Tschopp, Berven, & Chan, 2011) and the MacArthur Modified Admission Experience Survey (Swartz et al, 2002) are two such adaptations. To rewrite items regarding the admission process to cover pressures and coercion in respect of outpatient treatment was not easy, and I find the results wordy, such as the item "I had more influence than anyone else on whether I went to the mental health center".…”
Section: The Macarthur Perceived Coercion Scale (Mpcs)mentioning
confidence: 99%
“…The MacArthur Admission Experience Scale has been subjected to two adaptations for outpatient care. One is a combination of adapted items from the Admission Experience Scale and the Therapeutic Limit-Setting Scale (Neale & Rosenheck, 2000), called the Perceptions of Mental Health Services Questionnaire (Tschopp et al, 2011). The other is the MacArthur Admission Experience Survey (Modified) (Swartz et al, 2002).…”
Section: A Search For All Scales Of Experienced Coercionmentioning
confidence: 99%
“…Because these approaches to engagement and treatment are commonly used, ACT programs have been criticized for being paternalistic or even coercive (Anthony, Rogers, & Farkas, 2003; Dennis & Monahan, 1996; Gomory, 2001; Williamson, 2002). Prior research is mixed on the extent to which ACT teams provide services in a recovery oriented way (Kidd et al, 2010; Moser & Bond, 2009; Neale & Rosenheck, 2000; Rapp & Goscha, 2004; Tschopp, Berven, & Chan, 2011).…”
Section: Introductionmentioning
confidence: 99%